The Contribution of Innovation and Technology to Teacher Performance Improvement - Sherly; Sihombing, Humiras Betty Marlina; Dharma, Edy (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
Innovation and technology have become important elements in the transformation of education in the digital era. Teachers, as key agents of change in education, play a crucial role in integrating technology and implementing innovative methods to enrich students' learning experiences. This research is important to identify the extent to which innovation and technology are able to support teachers' tasks in delivering material more interactively and efficiently. This study uses a quantitative approach with a survey method of 30 teachers at Sultan Agung Private Junior High School Pematangsiantar. The results of the study show that there is a significant positive influence between the application of innovation and technology on improving teacher performance. Innovations in teaching methods allow teachers to be more creative in delivering material, while the use of technology facilitates better interaction with students and facilitates classroom management. Thus, this study emphasizes the importance of developing teachers' ability to innovate and use technology as a strategy to improve the quality of education. This research also provides implications for education policymakers to increase support for training programs and technology development in the school environment.